Enterprise Blockchain & AI Infrastructure: Powering the Future of Decentralized Healthcare – Part 1 - Rakhmilevich, Mark; Venkataraman, Mohan (Blockchain in Healthcare Today, 2025)
Decentralized healthcare is no longer a distant vision—it’s an emerging reality that demands secure, scalable, and intelligent infrastructure. This podcast explores how enterprise grade blockchain platforms and artificial intelligence are converging to create next generation health ecosystems – there is a significant value proposition that professionals are waking up to. Topics include: Drivers pushing the healthcare industry towards decentralized technology How blockchain and AI address data silos and trust issues in healthcare Critical components for decentralized healthcare—a secure data layer, intelligent automation, etc. How the Oracle blockchain platform meets scale, performance, and compliance needs in healthcare How AI and blockchain technically integrate How decentralized technologies with AI ensure compliance with HIPAA for data sharing Example of blockchain + AI solution delivering real value in healthcare How blockchain and AI are impacting supplier risk management in the pharmaceutical industry The next frontier for AI and blockchain in healthcare Whether you’re an enterprise CTO, innovation lead, or digital health strategist, the discussion delivers leading edge insight into the platforms and protocols shaping decentralized care—and how AI is supercharging it. Speaker Biographies Mark Rakhmilevich, Group VP, Product Management and Development Fintech, Blockchain, Transaction Management, Mission-Critical Systems, Oracle Corporation E-Mail: mark.rakhmilevich@oracle.com Mark Rakhmilevich is Vice President of Product Management and Development at Oracle, leading the Fintech, Blockchain, and Transaction Management portfolio within Oracle’s Mission-Critical Systems group. He drives technology and product strategy for key solutions including Oracle Blockchain Platform, Blockchain App Builder, Oracle Database Blockchain Tables, Tuxedo, Transaction Manager for Microservices, and the Fintech Data Platform initiative—delivering innovation both in the cloud and on-premises. With a focus on the complex needs of financial institutions, public sector, and enterprises across manufacturing, logistics, healthcare, and other industries, Mark guides global organizations in leveraging blockchain, digital assets, and data platforms to drive measurable outcomes—accelerating growth and innovation, deepening customer engagement, streamlining operations, reducing fraud and risk, and bringing to market innovative solutions that solve real-world economic and societal challenges. He plays a pivotal role in Oracle’s blockchain and digital assets strategy, working with customers and partners across sectors to move from experimentation to production—sharing industry use cases, advising on deployment architectures, and aligning technology with regulatory and business imperatives. Mark has been actively involved in numerous enterprise blockchain projects across industries and digital asset initiatives with financial services innovators worldwide. He’s actively exploring intersection of Blockchain and AI, where decentralized ledgers and smart contracts enable privacy-preserving model training and Agentic AI collaboration. A recognized thought leader, Mark is shaping Oracle’s innovation in Digital Assets, Decentralized Identity, and AI-powered compliance through the Fintech Data Platform initiative. He has spoken at global forums including the OMFIF Digital Money Summit and regularly contributes insights on Oracle Blockchain Blog and on LinkedIn. Mohan Venkataraman, Principal Consultant, Block10.ai With over 35 years in tech, Mohan has had the privilege of serving more than 100 clients. From 2013, he served as CTO of Chainyard, where he established the “Consulting and Advisory” Practice. His journey into blockchain began in 2015, and his team went on to deliver over 40 projects across industries from healthcare to fintech. Subsequently, he expanded the services into AI and machine learning solutions. Mohan’s work in healthcare is particularly notable, leveraging blockchain and AI for solutions such as The Health Wallet, secure document sharing, and transparent supply chains. He is a recognized speaker at forums like the Hyperledger Global Forum, and a contributor to several patent-pending blockchain solutions.. Today, under block10.ai, he offers independent advisory consulting. His focus is on blockchain, AI, and machine learning, helping clients refine their ideas, develop solid business models, and create implementation strategies.